Study on Sustained-Release Tablets of Tramadol Hydrochloride - Huo, Qing; Guo, Chenyang; Gu, Tianhao; Liu, Wanying (Asian Journal of Chemistry, 2014)
Tramadol hydrochloride has a potential role in the central nervous system of potent non-narcotic analgesics, no respiratory depression and cardiovascular reactions, is a non-morphine-like analgesics. In order to improve the analgesic effect time of tramadol hydrochloride, we study on 2 times a day for 12 h sustained-release tablets, single factor is determined by the release of different viscosity hydroxypropyl methyl cellulose (HPMC), identified by model K15M HPMC as hydrophilic matrix, orthogonal design study factors affecting sustained-release tablets, the prescription of 1000 tramadol hydrochloride sustained-release tablets is tramadol hydrochloride 69 g, carboxymethyl cellulose of sodium 20 g, hydroxypropyl methyl cellulose 27 g, PEG 15.41 g, ethyl cellulose 13.40 g, magnesium stearate 6 g, starch 2 g, the limitation of l, 2, 4, 8 h of dissolution for tramadol hydrochloride are 32, 42, 68 and 85 %, the average tablet weight 0.15 g, hardness 5.28 kg in the pharmacopoeia range. The stability of tablets is measured in the illumination of 2000-4000 LX, quality does not change and no degradation products, when the tablets are put in a high temperature of 80 °C, the surface of the tablets become yellow, so tablets should be sealed and placed in cool place.